Construção de cenários prospectivos para o ensino superior brasileiro - Carneiro, Francisco Stenio de Araújo (2010)
New administration planning methods were brought about to allow managing decisions taking mainly due the speedy transformations that we are experiencing nowdays among the business administration arena. Many of these methods, despite of being created to a precise goal, ended up by being used, partially or not, to other ones distincts from the originals. That’s the case of methods that deal with prospective scenarios and that yearly reveal themselves as vital tools to business strategic planning. This study aims to verify in the field of higher education, the viability of an instrument to construct scenarios basead on one of these methods in the case, the method Grumbach. Education field was choosed, as study object, because it is a fundamental research one to the achievement of human and economic development of our country, which, morever, has been experienced, nationally and internationally, numerous conversions. The strategies and paths used in the preparation on the scenarios proposed their achievement through fourteen steps. The evaluation of the results was positive with reference to an efficient and consistent achievement of future scenarios, and also with reference of providing subsidies to public policy lawmakers. It is concluded, then, that the structure applied serves the purpose of the study because of its easy operation and have great ability have generated all possible future scenarios of research, including the three scenarios required by Grumbach Method to be described.